An Opial-Type Inequality on Time Scales - Qiao-Luan Li; Wing-Sum Cheung (Abstract and Applied Analysis)
We establish some new Opial-type inequalities involving higher order delta derivatives on time scales. These extend some known results in the continuous case in the literature and provide new estimates in the setting of time scales.